The Impact of Digital Marketing and Brand Awareness on Purchasing Decisions with Brand Image as an Intervening Variable at 3-Star Hotels in Makassar - Arief, Arnie; Witarsana, I Gusti Agung Gede; Eppang , Buntu Marannu (Journal of Mandalika Review, 2024)
Abstract Background: Research on Digital Marketing, Brand Awareness, and Brand Image is necessary to determine which indicators most effectively influence consumer purchasing decisions. Previous studies have shown varying results, underscoring the importance of revisiting these variables. Differences in indicators for each variable, as well as the specific context of 3-star hotels in Makassar, contribute to the uniqueness of this research. Methodology: The population for this study includes guests staying at 55 3-star hotels in Makassar. The sample size, determined using the Isaac & Michael method, is set at 349 respondents. The research employs a descriptive quantitative approach and statistical data analysis. Data collection is conducted through surveys using questionnaires. Data analysis techniques include path analysis, with stages involving Outer Model Testing, Goodness of Fit Model Testing, and Inner Model Testing using Smart PLS. Findings: Brand Awareness has a positive but insignificant effect on Purchasing Decisions. Digital Marketing has a negative and insignificant effect on Brand Image. Digital Marketing has a negative and insignificant effect on Purchasing Decisions through Brand Image. Conclusion: Brand Awareness can impact purchasing decisions, although the effect is not significant, and Digital Marketing does not significantly affect either purchasing decisions or brand image. Therefore, 3-star hotels should improve their Brand Image and Digital Marketing performance and consider other variables and strategies to build a strong and positive brand image in the eyes of consumers. Keywords: Digital Marketing, Brand Awareness, Brand Image, Purchasing Decisions, Star Hotel